Brazil - Poverty Reduction, Growth, and Fiscal Stability in the State of Ceara : A State Economic Memorandum, Volume 2. Annexes - World Bank (Washington, DC, 2013)
Although the State of Ceara, in Brazil, is a model of good economic, and fiscal performance given its poverty status, recent analysis show poverty remains severe, in spite of significant reductions over the last decade. The combination of good governance, and sound fiscal management, industrial promotion, and public investments have been successful, but the report questions whether different policies, could have led to higher growth, and poverty reduction, or, whether it is simply a matter of time to further reduce poverty rates. Arguably, Ceara can continue to develop economically, based on favorable assets, such as agriculture, or tourism, on a large labor force with wages comparatively low by Brazilian standards, and on fiscal responsibility. But development is constrained by low productivity, low education levels, and by large populations living in stagnant regions, where water accessibility is limited. While alternatives either suggest to: strengthen the existing policy on industry development; focus on massive public investments, namely education, and infrastructure; or, exercise an explicit welfare strategy, recommendations stipulate improvements in education, development of public-private partnerships, removal of industrial incentives through reform policies, implementation of institutional framework for water resource management, and, overall social safety nets to reduce poverty.